Vrstniško nasilje v perspektivi dominantnih konstrukcij ženskosti in moškosti ter sovpadanja strukturnih neenakosti - Hrženjak, Majda (Šolsko polje, 2011)
Engendering as a continuous process of subjectivization and socialization disciplines human beings according to "gender-appropriate" norms. The more hegemonic and dominant specific constructions of femininities and masculinities are, the stronger is their pressure to shape "gender-appropriate" behaviors, reactions, attitudes, and so on. School-age children are in the process of identity negotiations and confl icts, and they are particularly sensitive and vulnerable to the oppressive influences of dominant constructions of femininities and masculinities. This article uses the concept of "dominant masculinities and femininities" to argue that gender as a social category can be a basis for developing violent behavior patterns among youth. The introduction of the concept of intersectionality demonstrates how structural inequalities based on ethnicity and class can influence the violent performance of gender. Empirical evidence illustrating these theoretical points of departure are taken from the Stamina international research project, which included thirty-eight semi-structured interviews with thirteen- to fourteenyear- old children about their experiences and reflections of school, family, leisure time, intimate relations, constructions of gender, and violence.
Keywords: peer violence; vrstniško nasilje; spol; gender; razlike med spoloma; structural inequalities; strukturne neenakosti; intersectionali; intersekcionalnost; education; vzgoja in izobraževanje